PENINGKATAN HASIL BELAJAR SEJARAH PADA MASA PANDEMI COVID-19 MELALUI PEMANFAATAN APLIKASI ZOOM PADA SISWA KELAS X TKJ.1 SMK NEGERI 1 SITUBONDO: SMK NEGERI 1 SITUBONDO - SUPADMI (Mitra Pendidikan, 2022)
The purpose of the study was to determine the increase in history learning outcomes during the Covid-19 pandemic through the use of the zoom application in class X TKJ.1 students of SMK Negeri 1 Situbondo. The type of research used by the author in this research is Classroom Action Research. Classroom Action Research (CAR) is an examination of activities that are intentionally raised, and occur in a class (Zaenal Aqib, 2009). The method used in this CAR is the method developed by Riel (2007) which divides the action research process from each cycle into the following stages: (1) planning; (2) implementation of actions; (3) data collection and analysis or in other methods known as the observation stage; and (4) reflection This research was conducted on students of class X TKJ.1 SMK Negeri 1 Situbondo which is located at Jl. Baluran No.17, North Kotakan, Kotakan, Kec. Situbondo, Situbondo Regency, postal code 68313 for 3 months starting from September 6, 2021 to November 20, 2021. In this study, the subjects of this study were students of class X TKJ.1 SMK Negeri 1 Situbondo in the odd semester of the 2021/ 2022, totaling 32 students. The data collection technique used in this classroom action research is through 1). Learning Outcomes Test, and 2) Observation Sheet. The data obtained from the observation and assessment of learning outcomes are classified based on student groups which are then analyzed by qualitative data analysis techniques. Based on the results of the discussion that has been described, it can be concluded that the use of the Zoom application can improve history learning outcomes for class X TKJ.1 SMK Negeri 1 Situbondo students during the COVID-19 pandemic.